(untitled) (Revista Archai, 2021)
The present work has the object of investigating the relation between emotion and persuasion in Xenophon’s Cyropaedia, not only by analyzing its lexical expressions, but also the emotional scenarios and the context in which they manifest. The Cyropaedia, usually considered as the epitome of Xenophon’s theory of leadership, shows us a crucial characteristic of Cyrus: his capacity of appealing to different emotions depending on the audience. This inquiry will allow us to trace the constitutive elements of a possible theory of emotions in Xenophon, which we will see, differs partially from the Aristotelian treatment in the Rhetoric, but also from his historiographic predecessors, Herodotus and Thucydides. Xenophon’s theory reveals a complexity that exceeds the mere appellation to emotions through speech as a means of persuasion and shows an intimate relation with the fourth century B.C. political and constitutional discourse.